Experimental Investigation of Citronella Oil as Bioadditive in Biodiesel Fuel on Diesel Engine Performance, Vibration and Emissions - Cahyono, Beny; Semin, Semin; Putri, Ifta Chariska (International Journal of Marine Engineering Innovation and Research, 2024)
Abstract The depletion of fossil fuels is one of the reasons for using alternative fuels such as biodiesel fuel. However, biodiesel has disadvantages such as higher density, lower heating value, high fuel consumption, and high nitrogen oxide (NOx) content compared to diesel. To improve this, it can be done by increasing the cetane number of the fuel by adding citronella (C) oil as a bioaditive. The purpose of this study is to determine the characteristics of biodiesel fuel after adding citronella oil, and to determine the effect of citronella oil addition on engine performance, vibration, noise and emissions. This research was conducted experimentally by adding citronella oil with variations in composition of 0.5%, 0.75%, 1%, 1.25%, and 1.5% of the volume of Biodiesel fuel (B30). The fuel was tested on a Yanmar single-cylinder diesel engine. Experimental results showed that the cetane number increased with the addition of citronella composition, with the highest cetane number in B30+C 1.5% fuel, which increased by 25.9% when compared to the cetane number of B30. From the performance test results, the diesel engine experienced an increase in performance in the form of power, torque, BMEP, as well as a decrease in vibration and noise when compared to B30 fuel. The lowest NOx emissions occurred at 2000 RPM with the largest load produced by fuel that had added citronella 1.5% with a decrease of 21.6% when compared to B30 fuel.